Research status and frontiers of renal denervation for hypertension: a bibliometric analysis from 2004 to 2023 - Jiaran Li; Xiaohan Zhang; Yuchen Jiang; Huan Wang; Xiongyi Gao; Yuanhui Hu; Bai Du (BMC, 2024)
Abstract Background Renal Denervation (RDN) is a novel non-pharmacological technique to treat hypertension. This technique lowers blood pressure by blocking the sympathetic nerve fibers around the renal artery, then causing a decrease in system sympathetic nerve excitability. This study aimed to visualize and analyze research hotspots and development trends in the field of RDN for hypertension through bibliometric analysis. Methods In total, 1479 studies were retrieved on the Web of Science Core Collection (WoSCC) database from 2004 to 2023. Using CiteSpace (6.2.R4) and VOSviewer (1.6.18), visualization maps were generated by relevant literature in the field of RDN for hypertension to demonstrate the research status and frontiers. Results The number of publications was found to be generally increasing. Europe and the United States were the first countries to carry out research on different techniques and related RDN clinical trials. The efficacy and safety of RDN have been repeatedly verified and gained increasing attention. The study involves multiple disciplines, including the cardiovascular system, peripheral vascular disease, and physiological pathology, among others. Research hotspots focus on elucidating the mechanism of RDN in the treatment of hypertension and the advantages of RDN in appliance therapy. Additionally, the research frontiers include improvement of RDN instruments and techniques, as well as exploration of the therapeutic effects of RDN in diseases with increased sympathetic nerve activity. Conclusion The research hotspots and frontiers reflect the status and development trend of RDN in hypertension. In the future, it is necessary to strengthen international collaboration and cooperation, conduct long-term clinical studies with a large sample size, and continuously improve RDN technology and devices. These measures will provide new options for more patients with hypertension, thereby improving their quality of life.